Penilaian EAFM pada Domain Teknik Penangkapan Ikan di Pulau Sangat Kecil Terluar dan Terdepan Indonesia (Studi Kasus Gugus Pulau Ayau,Raja Ampat) - Ilham Marasabessy; Vicky Rizky A. Katili; Muhamad Ali Ulat; Kadarusman Kadarusman; Amir Mahmud Suruwaky; Ismail Ismail; Mohamad Iksan Badarudin; Roger Tabalessy; Dwi indah widyayanti; Siswanto siswanto (Universitas Bengkulu, 2022)
Management and utilization of the fisheries resources in the Indonesia”s outermost tiny island, became a crucial concern, in order to ensure the economic improvement of the local communities and the sustainability of the ecosystem. This study aims to determine the value of the status of fisheries resources in the domain of fishing techniques across the Ayau Archipelago. Evaluation of EAFM implementation status is carried out by the adding up of the scores for each criterion and then dividing by the number of indicators. The index score is obtained from the average value of the flag model in the fishing technique domain. The total index value obtained is then analyzed using a multi-criteria system comparing the total index value of all attributes/indicators with the maximum total index. Arcmap GIS 10.3.1 for mapping was made to obtain the coordinates and area of the island. The results analysis of the composite value EAFM is 68.8%. Our Analysis also indicate that fishing capacity and fishing effort as well as crew certification of fishing boat have low scores with the index values of 315 and 60 respectively. Howover, small scale fisheries management in the Ayau archipelago attracts much special attention from related sectors for further improvement. the management of small-scale fisheries in the Ayau Islands from a technical and implementation point of view needs to be improved.